The design and simulation of a superconductive, COSL compatible comparator and high-speed superconductive analog-to-digital converter - Powell, I. A. (Ian Allan) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--University of Stellenbosch, 2004.